Survivability of P. oxalicum T3.3 bioformulation on carrier materials and storage temperature - Mad Saad, Maya Emira; K. M. S., Umi; Abdul Rahman, Nor'aini; Samsu Baharuddin, Azhari (AD Publications, 2018)
Good bioformulation play crucial roles in the successfully of commercialize biological control products. The development of bioformulation is necessary to improve product stability, delivery and bioactivity. The aim of this study is to assess the shelf life of P. oxalicum T3.3 conidia in the different ratio(1:1,1:2,2:1) of Biochar:Biocompost (BcBp) and Peat:Vermiculite (PtVm) and temperature (4ºC and room temperature) for 6 months. The results showed that P. oxalicum T3.3 was able to sustain highest viable cell (CFU) at 4ºC storage temperature. BcBp and PtVm have the highest cell viability at ratio 2:1 and 1:1, respectively. Both BcBp and PtVm showed potential carriers for the development of biofungicide for agriculture purposes.